2020
DOI: 10.1002/jcsm.12504
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric intervention in community‐dwelling older adults: a cluster‐randomized controlled trial

Abstract: Background In longevity societies, one of the most serious social issues is sarcopenia and/or frailty. Preventing them is important for maintaining independence and quality of life in the older population. This study investigated the effect of a self‐monitoring comprehensive geriatric intervention programme (CGIP) on physical function and muscle size in community‐dwelling older adults. We compared the effects of a CGIP using weekly class‐styled (CS) sessions and a home‐based (HB) programme. Methods The 526 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 56 publications
0
55
0
Order By: Relevance
“…Our previous study demonstrated that adding approximately 1,000 steps per day is a viable strategy for large-scale population-based intervention. 23 The strengths of this study are that we verified the association between daily step counts assessed by accelerometers in a large-scale cohort study of older adults living in a region and the prevalence of frailty as defined by two validated evaluation tools. The results for their association are robust, and our results may have potential for further generalization.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our previous study demonstrated that adding approximately 1,000 steps per day is a viable strategy for large-scale population-based intervention. 23 The strengths of this study are that we verified the association between daily step counts assessed by accelerometers in a large-scale cohort study of older adults living in a region and the prevalence of frailty as defined by two validated evaluation tools. The results for their association are robust, and our results may have potential for further generalization.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, our results indicate the possibility that the effect of increasing daily step count may be greater in people with lower daily step counts, suggesting that the “+10” (approximately 1,000 more steps than now), with the objective of a small increase in step count, may be effective for shut‐in or sedentary older adults with low step counts. Our previous study demonstrated that adding approximately 1,000 steps per day is a viable strategy for large‐scale population‐based intervention 23 …”
Section: Discussionmentioning
confidence: 99%
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…Of the nutrition studies that we found, one explored the role of protein, 31 three explored the role of vitamin D, 26,38,39 two explored the role of several nutrients, 3,41 and one explored the role of natural product (astaxanthin) supplements 40 . Seven studies 25,27–30,32,33 investigated the effects of multimodal interventions (defined as two or more approaches) on muscle mass. Articles also explored the associations of protein intake, 46,47 iron deficiency, 37,42 micronutrients, 35 calorie restriction, 43 nitrate dietary intake, 36 retrospective evaluation of early dietary supplementation, 44 and overall dietary intake and patterns 34 with several clinical outcomes and/or biomarkers of sarcopenia or cachexia.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“…The accelerometer displays were masked to prevent participants from checking their step counts. In addition to step counts (i.e., number of steps/day), moderate-to-vigorous physical activity (i.e., ≥3 metabolic equivalents; MET) was measured in terms of MET h/week [29].…”
Section: Methodsmentioning
confidence: 99%